2021
DOI: 10.3390/ph14121283
|View full text |Cite
|
Sign up to set email alerts
|

Association between Statin Use and Gastric Cancer: A Nested Case-Control Study Using a National Health Screening Cohort in Korea

Abstract: Concerns about the hazards of statins on the development and mortality of stomach cancers remain controversial. Here, we investigated the likelihood of incident gastric cancers and related mortality depending on statin exposure, statin type, and the duration of use. This nested case–control-designed study was composed of 8798 patients who were diagnosed with gastric cancer and matched with 35,192 controls at a 1:4 ratio based on propensity scores of age, sex, residential area, and income from the Korean Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…In total, 29 studies were selected for full-text screening based on prespecified selection criteria. Finally, 20 studies were selected for the meta-analysis [ 17 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 29 studies were selected for full-text screening based on prespecified selection criteria. Finally, 20 studies were selected for the meta-analysis [ 17 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Included studies also demonstrated that statins are even more protective against gastric cancer if patients take a higher dose over a longer duration of time [ 26 , 27 , 28 ]. Kwon et al [ 17 ] showed that a significant reduction in gastric cancer was observed among patients taking hydrophilic statins. Our subgroup analyses showed that pravastatin (hydrophilic) was associated with an insignificant reduction of gastric cancer, whereas rosuvastatin showed an increased risk of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atorvastatin is administered as a clinical treatment for hypercholesterolemia at 10–80 mg/day [ 26 ]. Several nationwide cohort studies have revealed that the administration of statins reduced the risk of GC and its overall mortality [ 27 , 28 ]. In several human cancer types, the antitumor mechanisms of statins are associated with the inhibition of HMGCR, which converts HMG-CoA to mevalonate [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%